The symbolic foundation of the music style - Snopkova, O.V. (Pedagogy of Higher and Secondary Education, 2006)
The scientific approaches in determining the point of music style, social and cultural preconditions of us forming are analyzed in the article, also discussed some questions of style forming, that found on the effect of the symbol as a cultural - marking form symbolical expression of images.